Impact assessment of cover crops on the risk of frost in the Anjou vineyard - Laetitia Bau; Thomas Chassaing (IVES Technical Reviews)
The increase in the frequency of spring frosts and the rising precocity of the phenological stages of the vine have been threatening the wine production in the Anjou vineyard for several years (Petitjean et al., 2022). In addition to these effects of climate change, the developing practices of grassing and sowing cover crops (Gaviglio, 2022) have the effect of modifying the vine’s microclimate and can increase frost damage (Hirschy et al., 2020). Hence, a study on the impact of cover crops and destruction method on the risk of frost was carried out in the Anjou vineyard.